Moving Business Excellence in Malaysia; Strategic Enables & Actions Under - IR 4.0 Initiatives - Ishak, Ismail (2018)
Already, a number of initiatives and organisations have been established at the national, state and regional level by both the Government and industry to develop plans and actions to strengthen various manufacturing industries. This support for and focus on manufacturing firms are important and create a strong platform. However, these programs have largely been developed independently and often have overlapping objectives and industry audiences.